Violência infantil no Brasil: uma análise das notificações compulsórias, 2011 - Susana Maria Moreira Rates (2014)
Introduction: Violence against children is universal and recognized as a public health problem. The true dimension of the issue is however a challenge to know due to the difficulties in establishing the circumstances in which violence takes place, the lack of uniformity, the need to centralize and organize the reports around the country as well asconceptual differences in typologies and under-reporting by a part of society and professionals. Objective: To describe violence reports against children from 0 to 9 years of age issued by the public health services in Brazil in 2011. Methods: The data used in this study were extracted from the Surveillance of Violence and Injuries of Notifiable Diseases Information System (Viva-SINAN). The frequency of selected variables was calculated by age group (0-1; 2-5 and 6-9 years of age) as well as their Prevalence Ratios according to the type of violence with IC of 95%. Results: Domestic environment is the main stage of aggression (73,6%), upon girls (54,3%), being the parents the aggressors (51,5%), inrepetition (43,6%) and the use of alcoholic drinks being reported in 23,8% of the cases. Negligence was the most often violence type reported (47,5%), followed by physical (38,5%) and sexual (37,0%) and also psychological (25,5%). The study of Prevalence Ratios (PR) indicated that physical violence is predominant among boys (RP 1,22; IC 95%: 1,16-1,28) more often among boys from 6 to 9 years of age (PR 1,19; IC95% 95% 1,12-1,27), people other than the parentes were the most prevalent aggressors (PR 0,76; IC95% 0,73-0,80). Sexual violence is predominant among girls; brown/black (PR 1,12; IC 95% 1,06-1,19) alsooccurring more often with girls from 6 to 9 (PR 1,12; IC95% 4,22-5,08), with more chance to occur at home (PR 1,38; IC 95% 1,29-1,48); the prevailing aggressors being persons other than the parents (PR 0,37; IC 95% 0,32-0,40). Psychological violence is predominant on girls;brown/black (PR 1,10; iC95% 1,03-1,18) with more chance to happen with girls from 6 to 9 (PR 2,95; IC 95% 2,69-3,23), at home (PR 1,40; IC 95% 1,29-1,53), the prevailing aggressors being persons other than the parents (PR 0,37; IC 95% 0,32-0,40). Psychological violence ispredominant on girls; brown/black (PR 1,10; IC 95% 1,03-1,18) with bigger occurrence among girls from 6 to 9 (PR 2,95; IC 95% 2,69-3,23), at home (PR 1,40; IC 95% 1,29-1,53), being individuals other than the parentes the most frequent aggressors (PR 0,90: IC 95% 0,85-0,96). Negligence occurred more often among boys (PR 1,33; IC 95% 1,27-1,39); regardless of color/race, more frequently among boys aged from 0 to 1 outside their homes, with their parentes as main aggressors (PR 2,60; IC 95% 2,47-2,74). Conclusion: Although reports areincreasing in the country, a direct consequence of policies implemented by the Ministry of Health, it is not possible to draw comparisons between regions because of the under-reports still existing. However, the results indicate the need to strengthen intersectoral actions aiming at extending the social protection and care network.